Type-1 fuzzy forecasting functions with elastic net regularization - İNAN, DENİZ (My University, 2022)
Fuzzy functions have recently been used for forecasting problems. The main concepts behind a fuzzy functions are to cluster the inputs using a fuzzy clustering method and to include the obtained membership grades and their non-linear transformations as new variables in the input matrix. Then, multiple linear regression models are solved for different clusters. However, adding related variables to the input matrix leads to the multicollinearity problem. Thus, the main contribution of the proposed method is to employ an elastic net in fuzzy functions to overcome the aforementioned problem. Two regularization terms occur in an elastic net that come from the ridge and the lasso regression. These regularization terms are optimized using the nested cross-validation approach to overcome the multicollinearity problem in the fuzzy functions method. Twelve practical time-series datasets are analyzed to evaluate the performance of the proposed fuzzy functions. The outstanding performance of the proposed method has been verified in terms of root mean squared errors and mean absolute percentage errors for the selected datasets.
Keywords: Sosyal ve Beşeri Bilimler; Ekonometri; Yöneylem; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Social Sciences and Humanities; Econometrics; Operational Research; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Engineering and Technology; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; OPERASYON ARAŞTIRMA VE YÖNETİM BİLİMİ; Ekonomi ve İş; Sosyal Bilimler (SOC); COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; OPERATIONS RESEARCH & MANAGEMENT SCIENCE; ECONOMICS & BUSINESS; Social Sciences (SOC); Genel Mühendislik; Elektrik ve Elektronik Mühendisliği; Mühendislik (çeşitli); Yönetim Bilimi ve Yöneylem Araştırması; Bilgisayarla Görme ve Örüntü Tanıma; Bilgisayar Bilimi Uygulamaları; Yapay Zeka; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Örgütsel Davranış ve İnsan Kaynakları Yönetimi; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; General Engineering; Electrical and Electronic Engineering; Engineering (miscellaneous); Management Science and Operations Research; Computer Vision and Pattern Recognition; Computer Science Applications; Artificial Intelligence; Computer Science (miscellaneous); General Computer Science; Organizational Behavior and Human Resource Management; Physical Sciences; Social Sciences & Humanities; Type-1 fuzzy functions; Elastic-net regularization; Forecasting; Non-linear forecasting; TIME-SERIES; ANFIS; REGRESSION; SELECTION; RIDGE